Konsep Ilmu Pendidikan Dasar Islam Berbasis Pada Tripusat Pendidikan - Laila Fajrin; Arifin, Zainal; Munastiwi, Erni (Diksi: Jurnal Pendidikan dan Literasi, 2025)
The research entitled “The Concept of Islamic Basic Education Based on the Tricenter of Education” aims to find out how important the tricenter of education is in basic Islamic education, especially for children. Carrying out a tricentre education study is important because many people in society hand over matters of religious education to schools, even though parents and the community have very important roles and functions as well. This research method is qualitative with a literature review approach. The results of this research are that Islamic basic education with a tricentral approach is very important to implement. So that education is not only focused on educational institutions, but rather the family environment and community have a sense of responsibility for basic Islamic education.